PEDAGOGY OF OBEDIENCE: RELIGION AND WORK IN NINETEENTH-CENTURY READING BOOKS - Morais, Cleidiane (Seven Editora, 2026)
This article analyzes the relationship between reading instruction, religion, and work in primary education in Ceará, Brazil, during the second half of the 19th century. Its main sources are the school textbooks used at the time, especially the reading books by Abílio Cesar Borges and the "Facílimo Method" by Emílio Achilles Monteverde. It argues that these printed materials, far from being limited to literacy, functioned as instruments for disseminating a Catholic Christian morality articulated within a project of social discipline. Through fables, short stories, maxims, and images, these books instilled values ​​such as obedience, resignation, fear, charity, and the valorization of work, contributing to the formation of docile, economically useful individuals adjusted to the prevailing order. The study shows that reading was conceived not as an autonomous practice or one geared towards pleasure, but as a means of internalizing moral and religious norms, frequently based on a pedagogy of fear and guilt. In this context, religion and work appear as complementary pillars in the construction of an ethic aimed at maintaining social hierarchy, especially with regard to the poor, for whom primary education was intended to train a disciplined and obedient workforce. At the same time, the role of the Church and the educated elites in legitimizing this order stands out, as well as the use of school textbooks as vehicles for a civilizing project that sought to reconcile progress, faith, and social control.